Mentally Subnormal Children: Probable Causes, Backgrounds, and Preventive Aspects - Titi Sunarwati Sularyo (Paediatrica Indonesiana, 1995)
A prospective study on 71 students in a special school for mentally subnormal functioning children in Jakarta was reviewed by physical examination, psychometric evaluation interviews and home visits. In the majority (87.5%) the IQ ranged from 70 to 90 Units (Wechsler scale). Of the 71 children, 4 7 (65.6 %) had somatic or biomedical known factors as etiology, while the other 24 (34.4%) were probably of sociocultural origin. This was surprising, since although the children had mentally subnormal intellectual functioning, the biomedical factors still played a high toll for it. Sociocultural factors, found out on home visits, such as unfavorable reproductive pattern of mothers, maternal deprivation, unwanted pregnancies, overprotective attitude, broken homes etc. were identified. For prevention, strengthening of the MCH care and family planning will be of utmost importance.